1999
DOI: 10.1590/s0100-879x1999000300006
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of p53 expression and proliferative assessment using PCNA in localized prostate carcinoma

Abstract: The surgical specimens from 51 men submitted to radical prostatectomy for localized prostate cancer were examined by immunohistochemistry using proliferation cell nuclear antigen (PCNA) monoclonal antibody to evaluate the proliferative index (PI). The relationship between PI, biological variables and p53 protein expression was evaluated by immunohistochemistry. PI was low in invasive localized prostate carcinoma (mean, 12.4%) and the incidence of PCNA-positive cells was significantly higher in tumors with p53 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2003
2003
2004
2004

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…Ki‐67 and PCNA have been used extensively as indicators of the proliferative state in cells and p120 protein has been considered to be associated with cell proliferation and has been demonstrated in most tumour cells 3,5,8,18,19 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ki‐67 and PCNA have been used extensively as indicators of the proliferative state in cells and p120 protein has been considered to be associated with cell proliferation and has been demonstrated in most tumour cells 3,5,8,18,19 …”
Section: Discussionmentioning
confidence: 99%
“…Leite et al. found that there was no statistical difference in PCNA values when biological parameters such as Gleason score were considered and concluded that proliferative activity is usually low in prostate carcinoma 19 . However, another study has shown that the percentage of PCNA‐positive nuclei increases with decreasing degree of differentiation 25…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in the p53 tumour suppressor gene are generally seen as a late event in progression of prostate cancer and are associated with androgen-independence, metastasis and poor prognosis. Leite et al concluded that, although p53 mutation is a rare event in prostate carcinogenesis, the detection of p53 protein by immunohistochemistry is common 72 . In this case it is associated with decreased apoptosis, increased histological grade and tumour stage.…”
Section: The Significance Of Key Regulators Of Apoptosis In the Develmentioning
confidence: 99%
“…Also according to Byrne et al p53 mutations contribute to progression of prostate cancer and the time period of tumour progression in patients with positive p53 is significantly shorter than those with p53 negative 79 . Proliferative activity determined using PCNA expression in prostate carcinomas is usually low but this correlates with positive p53 immunostaining 72 . A positive correlation between Ki 67 and p53 protein expression has also been found 80 but other findings contradict this.…”
Section: The Significance Of Key Regulators Of Apoptosis In the Develmentioning
confidence: 99%